2021
DOI: 10.1371/journal.pone.0253569
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of disorientation towards immunization on online social media after contrasting political communication on vaccines. Results from an analysis of Twitter data in Italy

Abstract: Background In Italy, in recent years, vaccination coverage for key immunizations as MMR has been declining to worryingly low levels, with large measles outbreaks. As a response in 2017, the Italian government expanded the number of mandatory immunizations introducing penalties to unvaccinated children’s families. During the 2018 general elections campaign, immunization policy entered the political debate with the government in-charge blaming oppositions for fuelling vaccine scepticism. A new government (former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Even rubella-related tweets are weak signals; we found that they have increased in recent years, particularly in response to news and related events. These results are consistent with SNS analyses of measles and other diseases conducted in other countries [ 19 , 21 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Even rubella-related tweets are weak signals; we found that they have increased in recent years, particularly in response to news and related events. These results are consistent with SNS analyses of measles and other diseases conducted in other countries [ 19 , 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…During the rubella epidemic in the Netherlands in 2013, the number of rubella cases and online news increased simultaneously, leading to an increase in tweets (Twitter posts) [ 16 ]. It is also reported that tweets increase in response to a main political event such as mandatory immunizations in Italy [ 21 ]. Public agencies such as the CDC and World Health Organization (WHO) were influential in disseminating information during the zika outbreak in 2015–2016 [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis carried out with text mining techniques on Italian tweets published between September, 2016 and August, 2017, showed a prevalence of neutral tweets (60%), followed by tweets against vaccination (23%), while the proportion of tweets in favor was the lowest (17%) ( 38 ). Finally, Ajovalasit et al ( 39 ) applied machine learning techniques to a corpus of vaccine-related Italian tweets posted in 2018, and identified 70% of tweets as favorable to vaccination, 16% as unfavorable and 14% as undecided. It is also interesting to note how the proportion of vaccine stances expressed in tweets might differ from that recorded through traditional surveys, on samples which are usually more representative of the Italian population than Twitter users.…”
Section: Discussionmentioning
confidence: 99%
“…Diaz et al [ 57 ] found that there was increased search activity regarding vaccines and infertility following the US Center for Disease Control and Prevention emergency approval of COVID-19 vaccines. Interactions on Twitter increased in response to political events, suggesting disorientation [ 83 , 85 ]. Mahroum et al [ 59 ] found that, in an influenza vaccine scandal (the Fluad case), regions affected by the scandal had more related web search activity, suggesting a localized search behavior.…”
Section: Resultsmentioning
confidence: 99%